PENGARUH MODEL PEMBELAJARAN FlIPPED ClASSROOM TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN SEJARAH (Studi Kuasi Eksperimen pada Peserta Didik kelas XI di SMAN 1 Bandung) - Siska Nurmalasari, - (2021)
ABSTRACT This research is an educational research that uses quasi-experimental rules about the history of learning conducted research in Class XI students majoring in Social Sciences. this research try to explain how to use the Flipped Classroom learning model to measure students' critical thinking when learning about history. The focus of this study was to see the effect of the Flipped Classroom model on students' critical thinking skills in history learning. Flipped Classroom it self is a strategy and learning method to flip (conventional) class conditions. If in conventional classroom conditions, the teacher presents the material in the classroom and is followed by assignments at home, then in this flipped classroom, the teacher assigns the task to students to learn the material to be learned. Researchers measure critical thinking skills because they see the condition of students who receive more information and news quickly through various media, so they are required to be able to filter various information by increasing their critical thinking skills.The research method used in this research is experimental research method because in the research there is treatment or manipulation. The Y variable in this study is the Flipped Classroom model and the X variable in this study is critical thinking. The reason this research uses a quasi-experimental type is because there is a control group or a control class. Through various stages from preparation, making instruments, pretest to posttest, the results of this study state that this flipped classroom model is effective for preparing students before learning history. The results of this study can be seen that after being given treatment and carrying out a recapitulation of students' critical thinking ability scores in the experimental class, the mean score was different between the pretest only 72.7 and the posttest score of the experimental class of 84.2. This was also shown by an increase in the value of the gain in students' critical thinking ability in the experimental class by 0.42. Flipped Classroom, including a current learning model, emphasizes that students get the value and essence of historical subject matter by utilizing technology to make learning more attractive to students and can further trigger students to improve critical thinking skills. Keywords: Flipped Classroom, critical thinking, History Learning.